Intraocular T-cell Lymphoma: Clinical Presentation, Diagnosis, Treatment, and Outcome. (3rd September 2017) - Chaput, Florence; Amer, Radgonde; Baglivo, Edoardo; Touitou, Valerie; Kozyreff, Alexandra; Bron, Dominique; Bodaghi, Bahram; LeHoang, Phuc; Bergstrom, Chris; Grossniklaus, Hans E.; Chan, Chi-Chao; Pe'er, Jacob; et al.
ABSTRACT: Purpose : To report on the clinical data of seven patients with T-cell intraocular lymphoma (IOL). Methods : Retrospective case series. Results : Seven immunocompetent patients, 12 eyes, 6 women, with T-cell-IOL were included from five countries. Mean age was 53.5 years (range: 25–82). Four patients had systemic-ocular lymphoma, two had CNS-ocular lymphoma, and one had systemic-CNS- ocular lymphoma. Vitritis was the most frequent clinical sign, followed by anterior uveitis and serous retinal detachment. Cytopathologic examination was performed on all ocular specimens (vitreous in six and iris mass biopsy in one patient). Adjunctive diagnostic procedures included immunohistochemistry, molecular tests, and cytokine profiling of vitreous samples. Treatment modalities included systemic chemotherapy (five patients), intravitreal methotrexate (three patients), globe radiotherapy, and intrathecal chemotherapy. Mean survival from diagnosis was 21.7 months (range: 2–69). Two patients are still alive. Conclusions : T-cell IOL has variable clinical manifestations and prognosis. Systemic involvement, SRD, and vitreoretinal involvement were frequently observed.